Voice From the Frontline: A Qualitative Exploration of Nurses' Views on Schizophrenia Therapy Adherence in Indonesia - Wardani, Ice Yulia; Hamid, Achir Yani; Daulima, Novy Helena Catharina; Asih, Sally Rahadi; Nasution, Riska Amalya (Politeknik Kesehatan Kemenkes Mamuju, 2026)
Schizophrenia is a severe chronic mental disorder characterized by symptoms that affect human thought processes, emotions, and behavior. This study aimed to explore nurses' perspectives on therapy adherence among individuals with schizophrenia in Indonesia, focusing on types of therapy programs, causes of non-adherence, consequences of non-adherence, barriers to adherence, and strategies for improving continuity of care. A qualitative phenomenological approach was employed, involving in-depth interviews with 11 nurses purposively selected from psychiatric hospitals and mental health clinics across Indonesia. Participants had at least three years of experience in schizophrenia care. Data were analyzed using the Colaizzi method to identify themes and subthemes. Five key themes emerged: (1) Types of therapy programs (nursing therapy, psychopharmacology, psychotherapy); (2) Causes of non-adherence (negative attitudes, lack of family support, drug side effects, healthcare system challenges, economic barriers); (3) Consequences of non-adherence (relapse, rehospitalization, social and familial impacts); (4) Barriers to adherence (nurse-related, doctor-related, patient-related, and family-related obstacles); and (5) Continuity of care (increasing resources, health collaboration, service integration). Nurses emphasized the need for multidisciplinary collaboration and systemic improvements to enhance adherence. The study highlights the multifaceted challenges in achieving therapy adherence among schizophrenia patients in Indonesia. Addressing these issues requires tailored interventions, stronger family and healthcare provider support, and integrated care models. These findings can inform policy and practice to reduce relapse rates and improve patient outcomes.